Outcome of data quality assessments of maternity records across 17 health facilities in Migori County, Western Kenya - Anthony Wanyoro; David Ogolla; Rikita Merai; Christopher Otare; Ruth Simotwo; Grace Mutindi; Everline Mumo; Dilys Walker; Phelgona Otieno (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Reliable, complete and accurate documentation of key health indicators form a critical part of quality of care to improve outcomes of pregnancy especially when dealing with preterm labor. Unfortunately, this is often not achieved in the rural areas in low- and middle-income nations due to a myriad of challenges, including lack of tools, low staffing, task shifting and inadequate training. Poor reporting from the source facilities lead to inaccuracies of data reported to the central registry at the Ministries of Health (MOH) which compounds the problem. As part of a large cluster randomized trial that used facility data as a primary source, we explored whether data quality assessments (DQAs) combined with facility-level mentorship, feedback and upgrades of patient chart storage space improved the quality of routine data in maternity units in a rural county in Kenya. # Methods Within the East Africa Preterm Birth initiative, we conducted three DQA's sequentially in 17 selected health facilities, in Migori County, Kenya. The process involved reviewing of key indicator data collected from the maternity register over a period of time while noting gaps in documentation. We also compared the concordance of data reported from the maternity register into the facility-level integrated service delivery form (MOH 711). Each DQA was followed up with targeted trainings and feedback on areas that needed strengthening. Over the period, we also renovated several facilities' documents storage spaces for safety and better traceability of patient's charts. # Results Results show that over time the patients' charts traceability and the quality of key indicator data captured in the maternity register improved significantly. The concordance of data reported from the primary source document to the central registry through the data capture tool MOH 711also showed significant improvement over time. # Conclusions Targeted regular DQA with facility-level mentorship and upgrades in records storage can improve data capture, patient-records retrieval and quality of data reported to the MOH; ultimately helping in improving the care for preterm cases.